Chemoprevention of esophageal cancer with esomeprazole and aspirin therapy: efficacy and safety in the phase III randomized factorial AspECT Trial - Jankowski, JJ; de Caestecker, JDC; Love, SBL; Reilly, G; Ang, YA; Ragunath, KR; Tucker, AT; Penman, IP; Rodgers, CR; Neale, JN; Roffe, ER; Brooks, CB; et al. (American Society of Clinical Oncology, 2018)
Esophageal adenocarcinoma (EA) is the sixth most common cause of global cancer death. We rely on endoscopy screening to identify and monitor patients with Barrett’s esophagus (BE) and find neoplastic lesions early enough to manage their EA. This approach has a modest effect on EA supported by low quality evidence. We evaluated the efficacy of aspirin and high dose acid suppression in preventing EA in patients with BE.